Pluralisme dan Integrasi Agama dalam Kebhinekaan dan Keberagaman Indonesia - Fakhiratunnisa, Safira Aura; Arista, Virandra Adhe; Widopuspito, Adena; Ningrum, Tika Kusuma; Firdaus, Arista Aulia (Lembaga Yasin AlSys, 2022)
Relationships between religions open every gate that forms a unique relationship. But it should be borne in mind that throughout the history of religion, religion has had a